Safety and Efficacy of Percutaneous Coronary Intervention via Transradial Versus Transfemoral Approach in Bypass Grafts. (February 2018) - Dai, Yuxiang; Li, Chenguang; Zhang, Feng; Yang, Ji'e; Chang, Shufu; Lu, Hao; Yang, Hongbo; Huang, Zheyong; Qian, Juying; Ge, Lei; Ge, Junbo
We compared the efficacy and safety of the transradial approach percutaneous coronary intervention (TRA-PCI) and transfemoral approach percutaneous coronary intervention (TFA-PCI) for bypass grafts lesions. Patients (n = 184) were retrospectively enrolled. Less contrast was used during the procedure in the TRA group than in the TFA group, 201.5 (45.5) mL versus 221.5 (49.1) mL, P = .004, although fluoroscopy time was longer in the TRA group, 22.5 (6.3) minutes versus 20.3 (6.1) minutes; P = .017. The incidence of net adverse clinical events (NACEs) was lower in the TRA group than in the TFA group (3.1% vs 8.8%, respectively, P = .111). The incidence of Bleeding Academic Research Consortium type 3 and 5 bleeding (0% vs 5.5%, respectively, P = .022) was significantly lower in the TRA group than in the TFA group. For 1-year outcomes, there was no difference in the incidence of major adverse cardiovascular events (7.5% vs 9.9%, respectively, P = .569). In conclusion, TRA-PCI was associated with a lower rate of in-hospital NACEs mainly attributed to lower rates of major bleeding. The TRA-PCI showed comparable feasibility and efficacy in bypass grafts as compared with TFA-PCI when carried out by experienced operators.